The hidden treasure of Black ASL : its history and structure - McCaskill, Carolyn; Lucas, Ceil; Bayley, Robert, 1943-; Hill, Joseph Christopher (Gallaudet University Press, 2011)
"[This book], originally published in 2011, presents the first sociohistorical and linguistic study of Black American Sign Language. Based on the findings of the Black ASL Project, which undertook this unprecedented research, Hidden Treasure documents the stories and language of the African American Deaf community. With links to online video content that includes interviews with Black ASL users, this volume is a groundbreaking scholarly contribution and a powerful affirmation for Black Deaf people. This paperback edition includes an updated foreword by Glenn B. Anderson, a new preface that reflects on the impact of this research, and an expanded list of references and resources on Black ASL. The online supplemental video content is available at the Gallaudet University Press YouTube Channel"--Publisher.